Exploring the Impression of Irrigation Management Techniques on Crop Harvests and Water Habit Efficiency - Hussein Layth; Ramadan Ghazi Mohamad; Prakash Akula (SHS Web of Conferences, 2025)
In the cumulative global food claim and water shortage scenario, well-organized irrigation management has become dangerous for sustainable agriculture. Out-dated irrigation methods often lead to considerable water wastage and do not enhance crop incomes, self-importance noteworthy trials for farmers. This study aims to investigate the influence of numerous irrigation management techniques on crop profits and water use efficiency (WUE). It emphasizes linking outdated methods with current methods such as leak irrigation, irrigator systems, and subsurface irrigation to regulate their efficiency in augmenting WUE and gathering efficiency. The future scheme contains the enactment of a WUE procedure to estimate and associate the presentation of these irrigation methods. Data on water customs and crop harvests are together from tentative plots, and the WUE is designed to evaluate the effectiveness of each method. This proportional analysis is predictable to expose that contemporary irrigation methods, predominantly drip irrigation, significantly increase WUE and harvest produces associated with outdated methods. Consequences from the learning specify that accepting progressive irrigation equipment such as drip irrigation can lead to considerable water investments and advanced cultivated crops. Drip irrigation protests the maximum WUE and crop harvest enhancements. These conclusions highlight the standing of augmenting irrigation applied to attain maintainable water usage and exploit crop construction if appreciated commendations for agriculturalists and representatives.